Quantifying the fate of wastewater nitrogen discharged to a Canadian river - Jason J. Venkiteswaran; Sherry L. Schiff; Brian P. Ingalls (Canadian Science Publishing, 2019)
Addition of nutrients, such as nitrogen, can degrade water quality in lakes, rivers, and estuaries. To predict the fate of nutrient inputs, an understanding of the biogeochemical cycling of nutrients is needed. We develop and employ a novel, parsimonious, process-based model of nitrogen concentrations and stable isotopes that quantifies the competing processes of volatilization, biological assimilation, nitrification, and denitrification in nutrient-impacted rivers. Calibration of the model to nitrogen discharges from two wastewater treatment plants in the Grand River, Ontario, Canada, show that ammonia volatilization was negligible relative to biological assimilation, nitrification, and denitrification within 5 km of the discharge points.